LAND ACQUISITION ESTIMATE FOR THE BANDUNG INTRA-URBAN TOLL ROAD (BIUTR) CONSTRUCTION PROJECT - Asyari, Ahmad Syuhada Islami; Muhammad, Garda Asa; Sari, Dian Apita; Kinesti, Ginaris; Suranata, Pasya; Somantri, Lili; Anggraini, Tania Septi (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2025)
The Bandung Intra-Urban Toll Road (BIUTR) serves as the government's initiative to address persistent traffic congestion in Metropolitan areas. However, A critical challenge in realizing this infrastructure is the land acquisition phase, which demands precise estimates and a comprehensive approach. This research aims to calculate the extend and monetary value of land impacted by the construction of BIUTR using a Geographic Information System (GIS) approach and spatial modeling. The research was conducted by establishing a 60-meter buffer zone on both sides of the toll road route as a road space. The analytical indicate that the BIUTR project will cross 14 sub-districts in Bandung City with a total affecting a total land area of 3,503,671.63 m² and with compensation value of more than IDR 70 trillion. Several sub-districts such as Cinambo, Cibeunying Kidul, and Cibeunying Kaler have high compensation values due to high land values and residential density. Result from his research highlight the necessity of conducting on fostering community engagement to develop a land acquisition strategy that is fair, efficient and minimize potential conflicts. emphasizes the importance of field verification and community participation in formulating a fair, efficient, and conflict-free land acquisition strategy. Keywords : Toll road, land acquisition, GIS, land value estimation, Bandung